2020
DOI: 10.5114/pg.2019.86806
|View full text |Cite
|
Sign up to set email alerts
|

The influence of nutritional status on the incidence of postoperative complications in patients following distal pancreatectomy

Abstract: Introduction: Malnutrition is a common problem in hospitalised patients. The immunological, inflammatory, and nutritional status of patients significantly influences the postoperative outcome. Aim: To assess and analyse the influence of the nutritional status on postoperative complications in patients following distal pancreatectomy. Material and methods: The analysis included 50 patients operated in a large centre of gastrointestinal surgery. The clinicopathological parameters were analysed, and the nutrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…A low PNI has recently been recognized to predict iatrogenic toxicity and complication in oncologic patients undergoing surgery or chemotherapy [ 38 , 55 ]. Low PNI has been associated with severe acute adverse events (i.e., toxicity of grade ≥ 3) of any type in HNC patients treated with radical or adjuvant radiotherapy [ 39 ], without distinction of single toxicity type.…”
Section: Discussionmentioning
confidence: 99%
“…A low PNI has recently been recognized to predict iatrogenic toxicity and complication in oncologic patients undergoing surgery or chemotherapy [ 38 , 55 ]. Low PNI has been associated with severe acute adverse events (i.e., toxicity of grade ≥ 3) of any type in HNC patients treated with radical or adjuvant radiotherapy [ 39 ], without distinction of single toxicity type.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that impaired NS is associated with higher perioperative morbidity following pancreatectomy and lower survival in PC patients. It has been reported that the poor NS was associated with a higher number of infections, delayed wound healing, impaired blood clotting, and vessel wall fragility and generally a higher number of postoperative complications following pancreatectomy [4][5][6]. It is also known that malnutrition is associated with deteriorated humoral and cellular immune response [6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the poor NS was associated with a higher number of infections, delayed wound healing, impaired blood clotting, and vessel wall fragility and generally a higher number of postoperative complications following pancreatectomy [4][5][6]. It is also known that malnutrition is associated with deteriorated humoral and cellular immune response [6]. Systemic inflammation is considered a significant indicator of a poor prognosis in PC patients [3,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The neoadjuvant time period thus serves as an ideal time for targeted interventions to improve patient comorbidities, nutritional indices, and functional condition before major oncologic surgery (i.e., prehabilitation). Patients with a high frailty index or poor nutritional status are also at risk for higher rates of postoperative morbidity and mortality 23,24 . Patients with potentially resectable PDAC who underwent prehabilitation with more than 60 min of physical activity a week experienced an increase in health‐related quality of life and physical function 25 .…”
Section: Rationale For Neoadjuvant Therapymentioning
confidence: 99%